BENTENG KARAKTER: SINERGI IMAN DAN PSIKOLOGI PENDIDIKAN AGAMA KRISTEN - Yermianti Bine (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
This study aims to formulate a holistic character development model through the integration of Christian faith and educational psychology in Christian Religious Education. The study is based on the need for a more systematic approach to character formation in response to moral challenges and the weakening of Christian values among students. This research employed a qualitative literature review by examining books, journal articles, and relevant academic sources on character education, Christian Religious Education, and educational psychology. The data were analyzed thematically to identify key concepts, relationships among ideas, and their implications for character formation. The findings show that the integration of Christian faith and educational psychology strengthens character development through five main dimensions: spiritual, moral, cognitive, affective, and social development. This integration also reinforces the role of Christian Religious Education teachers as facilitators who not only teach faith-based values but also accompany students’ psychological and personal growth. In conclusion, the synergy between Christian faith and educational psychology provides a conceptual foundation for holistic character development in Christian Religious Education. ABSTRAK Penelitian ini bertujuan merumuskan model pembinaan karakter holistik melalui integrasi iman Kristen dan psikologi pendidikan dalam Pendidikan Agama Kristen. Kajian ini dilatarbelakangi oleh kebutuhan akan pendekatan pembentukan karakter yang lebih sistematis di tengah tantangan moral dan melemahnya nilai-nilai Kristen pada peserta didik. Penelitian menggunakan metode kualitatif dengan pendekatan studi pustaka terhadap buku, artikel jurnal, dan sumber akademik relevan yang membahas pendidikan karakter, Pendidikan Agama Kristen, dan psikologi pendidikan. Data dianalisis secara tematik untuk mengidentifikasi konsep-konsep utama, hubungan antargagasan, serta implikasinya bagi pembinaan karakter. Hasil kajian menunjukkan bahwa integrasi iman Kristen dan psikologi pendidikan memperkuat pembinaan karakter melalui lima dimensi utama, yaitu perkembangan spiritual, moral, kognitif, afektif, dan sosial. Integrasi ini juga menegaskan peran guru Pendidikan Agama Kristen sebagai fasilitator yang tidak hanya mengajarkan nilai-nilai iman, tetapi juga mendampingi pertumbuhan psikologis dan personal peserta didik. Dengan demikian, sinergi antara iman Kristen dan psikologi pendidikan memberikan landasan konseptual bagi pembinaan karakter yang holistik dalam Pendidikan Agama Kristen.